ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Multidrug resistance (MDR) in cancer is driven by hypoxia, elevated antioxidant capacity, and drug efflux. Herein, a universal MDR-reversal nanoplatform based on hyaluronic acid (HA)-templated manganese oxide nanosheets (MH NSs) was developed through a biomineralization strategy. The coexistence of Mn(II)/Mn(III)/Mn(IV) endows MH NSs with coordinated multienzyme-like reactivity, including peroxidase (POD)-like ROS amplification, glutathione oxidase (GSHOx)-like redox disruption, and catalase (CAT)-like hypoxia relief, which collectively remodel the tumor microenvironment and dismantle MDR defenses. The platform exhibits broad drug-loading compatibility through multiple interactions, including electrostatic binding, metal-ligand coordination, and hydrophobic encapsulation. Using doxorubicin (DOX) as a model drug, DOX-loaded MH NSs (MH-DOX) achieve CD44-targeted delivery, clathrin-mediated endocytosis, and evasion of efflux clearance. Mechanistically, the CAT-like activity of MH NSs relieves hypoxia and suppresses the HIF-1α/MDR1/P-gp axis, the POD-like catalysis enhances ROS accumulation to activate the apoptotic cascade, and the GSHOx-like function depletes intracellular GSH and inhibits GPX4 to induce ferroptosis. Notably, MH NSs supports DOX intersystem crossing, enabling ultrasound-triggered production of 1O2 and ·OH. Acting in concert with the redox cascades, MH-DOX synergistically overcomes MDR barriers, enabling dual apoptosis-ferroptosis induction and significantly enhancing DOX sensitivity. Collectively, MH NSs represent a programmable nanozyme platform broadly applicable to redox-regulated drug delivery and resistance modulation.